Isolation and gene expression at different growth and infection stages of Ganoderma boninense cyclophilin encoding cDNAs - Lim, Fook Hwa (2013)
Oil palm, the major crop planted in Malaysia, is subjected to various diseases such as Basal Stem Rot (BSR) disease. The disease is mainly caused by Ganoderma boninense. However, studies of the fungal infection mechanism and the biological processes involved are still very limited. Fungal cyclophilin (CYP) has been reported to be involved in the pathogenicity of fungi. However, the involvement of CYP in the pathogenicity of G. boninense has not been reported. The main objective of this study was to isolate cDNAs encoding CYPs and to profile the expression levels of these genes during different growth and infection stages in G. boninense. In this study, five full-length cDNAs encoding CYP have been successfully amplified by polymerase chain reaction (PCR) from G. boninense. They were classified as different family members of CYP because significant differences could be observed on their coding sequence and 5’ or 3’ un-translated regions (UTRs). An in-vitro infection test has also been developed by infecting six months old oil palm plantlets with clumps of G. boninense mycelium in a 250 ml flask incubated at 28 °C for a duration of eight weeks. Control samples were also prepared by growing either the fungus or the oil palm plantlet in a flask. The fungal samples were collected every two weeks. The infected samples were verified by dissecting the basal stem of the infected oil palm plantlets, detection of Ganoderma using Ganoderma Selective Media (GSM), PCR and confirmation of Ganoderma species with Multiplex PCRDNA Kit. The findings indicated that G. boninense was detected in most of the infected plantlets. For real-time quantitative PCR (qPCR) optimization, a total of seven potential fungal reference genes were tested. α-Tubulin, β–tubulin and eEF2 were found to be the most stable reference genes. The expression of five CYP genes in different types of fungal tissues and infecting mycelium tissues were studied using the qPCR approach and normalized with the reference genes above. Based on the expression patterns, the potential functions of the CYP transcripts were predicted to be involved in the development of basidiomata (GBcyp201), normal cell growth (GBcyp202), stress response (GBcyp203) and fungal pathogenicity (GBcyp205). This work provided genetic information on CYPs encoded by G. boninense and predicted the functions of these CYPs especially in fungal pathogenicity which could be further studied and confirmed. This information may be essential in understanding the molecular infection pathway of G. boninense. Besides that, qPCR for G.boninense gene expression study has been optimized and this method could be used to study the expressions of other genes in G. boninense.